Long-term trends of tick-borne pathogens in regard to small mammal and tick populations from Saxony, Germany - Galfsky, Daniel (Parasit Vectors, 2019)
BACKGROUND: Rodents are important in the life-cycle of ticks as hosts for immature developmental stages. Both rodents and ticks are of public health interest as they are reservoirs and vectors for different tick-borne pathogens (TBP). The aim of this study was to reassess the prevalence of TBP in previously studied areas of the city of Leipzig (Saxony, Germany). METHODS: In the years 2015–2017 rodents and ticks were collected in parks and forest areas in Saxony. DNA was extracted from the rodents, attached and questing ticks. Samples were screened for the presence of Anaplasma phagocytophilum, Babesia spp., Borrelia burgdorferi (s.l.), “Candidatus Neoehrlichia mikurensis” (CNM), Bartonella spp., Hepatozoon spp. and Rickettsia spp. using PCR methods. Rodent, attached nymph and questing tick (nymph and adult) samples were tested individually, while attached larvae were further processed in pools. RESULTS: A total of 165 rodents (Apodemus agrarius, n = 1; A. flavicollis, n = 59; Arvicola terrestris, n = 1; Myodes glareolus, n = 104), 1256 attached ticks (Ixodes ricinus, n = 1164; Dermacentor reticulatus, n = 92) and 577 questing ticks (I. ricinus, n = 547; D. reticulatus, n = 30) were collected. The prevalence levels in rodents were 78.2% for Bartonella spp., 58.2% for CNM, 49.1% for B. burgdorferi (s.l.) 29.1% for Rickettsia spp. and 24.2% for Hepatozoon spp. The minimal infection rates (MIR) in attached larvae ticks were 39.8% for Rickettsia spp., 32.7% for Bartonella spp., 7.1% for CNM and 8.8% for B. burgdorferi (s.l.) and the prevalence rates in attached nymphs were 33.7% for Bartonella spp., 52.9% for Rickettsia spp., 13.5% for CNM and 11.3% for B. burgdorferi (s.l.) Both rodents and attached ticks were negative for Babesia spp. The prevalence in questing ticks was 18.2% for Rickettsia spp., 7.3% for CNM, 6.4% for B. burgdorferi (s.l.) and 1.4% for Babesia spp. All tested samples were Anaplasma-negative. Sequencing revealed the occurrence of 14 identified species. CONCLUSIONS: This research is the first evaluation of the prevalence for Hepatozoon spp. in rodents from Germany. In comparison to earlier studies, detected pathogens species remained the same; however, the prevalence for particular pathogens differed.